On the Arab revolts and the Iranian revolution power and resistance today - Adib-Moghaddam, Arshin (Suspensions. Contemporary Middle Eastern and Islamicate thought, 2014)
On the Arab Revolts and the Iranian Revolution: Power and Resistance Today is the first comparative analysis of two central political events that have altered our world forever: the Arab uprisings which started in Tunisia, and the Iranian revolution in 1979. Adib-Moghaddam argues that the dialectics of power and resistance are truly universal and that they are unfolding within a globalised political context that is increasingly interconnected.